Auditory information reduces response time for ball rotation perception, increasing counterattack performance in table tennis - Fujita, R. A.; Santos, D. P. R.; Barbosa, R. N.; Palucci Vieira, L. H.; Santiago, P. R. P.; Zagatto, A. M.; Gomes, M. M (Research Quarterly for Exercise and Sport, 2023)
Purpose: Identifying the magnitude of ball rotation is critical to reduce response time, aiming to improve table tennis performance. This study analyzed the influence of auditory and visual information on the perception accuracy and counterattack performance of table tennis players. Methods: Twenty-two high-level table tennis players (22.5 ± 6.1 years, 71.2 ± 9.8 kg, 173.5 ± 7.7 cm) performed two tasks. In the first task, the athletes analyzed audio and video files of the forehand movement on a computer screen with auditory, visual, and combined information and, as soon as possible, chose the ball spin type on a keyboard: fast (spinning ball forward at 140 rotations per second (rotations/s); medium (105 rotations/s); slow (84 rotations/s); or flat hit (70 rotations/s). In the second task, the athletes performed 80 counterattacks (forehand movement) at the table on a target (68x38 cm) with and without auditory information. Results: Friedman`s ANOVA revealed a significant effect of condition for perception accuracy (p < .001). Post hoc tests showed higher perception accuracy in the combined and visual conditions. ANOVA also revealed a significant effect of condition for response time to perceive ball rotation (p < .001). The response time was shorter in the combined condition than the other conditions for all spin types. Kendall`s analyses showed no significant correlations between perception accuracy and response time in any ball spin type. Regarding the counterattack performance, the Wilcoxon signed-rank test indicated higher performance when auditory information was available (p = .022). Conclusions: As auditory information influences the response time and counterattack performance, it seems crucial for trainers and athletes to explore and include auditory perception training methods.